Opportunities for antibiotic stewardship in emergency department or hospitalized patients with asymptomatic bacteriuria: identifying risk factors for antibiotic treatment - Morgan L. Bixby; Brian R. Raux; Aakansha Bhalla; Christopher McCoy; Elizabeth B. Hirsch (Cambridge University Press, 2022)
Antibiotic treatment of asymptomatic bacteriuria (ASB) is considered inappropriate and may lead to adverse events. This 2-center, retrospective cohort study including emergency department or inpatient adults identified pyuria (odds ratio, 2.43; 95% confidence interval, 1.17-5.01; P = .02) as the only independent risk factor for antibiotic treatment of ASB.